Does Examination Stress affect Brain Oscillations during Memory Tasks in the Luteal Phase? - Iqbal, Muhammad Naeem; Ashraf, Asfa; Iqbal, Iqra (PSM Biological Research, 2019)
Stress leads to an increase in the release of glucocorticoids from the adrenal cortex. There are conflicting results regarding the effect of stress on memory. pending update,